I-V performance analysis of flexible back Illuminated Dye Sensitized Solar cells (DSSCS) with various platinum catalyst contents - Shamsudin N.H.; Shafie S.; Ab Kadir M.Z.A.; Ahmad F.; Chachuli S.A.M.; Sulaiman Y. (Institute of Physics Publishing, 2023)
Catalysts; Deposition; Dyes; Electrodes; Electrolytes; Platinum; Back-illuminated; Conducting tests; Counter electrodes; Fabrication method; Higher efficiency; Light penetration; Nanotechnology revolution; Platinum catalysts; Dye-sensitized solar cells